Low-grade mucoepidermoid carcinoma of the parotid gland in a 5-year-old child: The youngest reported case from India - MATTA, HARSH PREET; Miglani, Ripan; Kaur, Manjeet; Kalayanpur, Tejas (Indian Journal of Case Reports, 2026)
Mucoepidermoid carcinoma (MEC) of the parotid gland is scarce in the pediatric group and is exceedingly uncommon in children under 6 years. In spite of being the most frequent malignant salivary gland tumor in children, the majority of cases are reported in older age groups. Only a few cases in children under 5 years have been documented worldwide, and the youngest of these previously reported Indian cases was a 6-year-old child. We report a rare case of lowgrade MEC of the parotid gland in a 5-year-old boy, describing the youngest reported case from India to date. The presenting complaint was a painless parotid swelling, and pre-operative imaging and fine-needle aspiration cytology (FNAC) were suggestive of pleomorphic adenoma. FNAC has limited sensitivity in pediatric salivary gland tumors, particularly in low-grade MEC, due to superimposing cytomorphological features with benign lesions. The management comprised superficial parotidectomy with facial nerve preservation, with histopathological examination confirming low-grade MEC with clear margins. This case highlights the rarity of this condition, diagnostic pitfalls and limitations of FNAC, and the significance of histopathological confirmation.